Computational analysis of rotating flow of hybrid nanofluid over a stretching surface. (December 2022) - Lei, Tongfei; Siddique, Imran; Ashraf, Muhammad Kamran; Hussain, Sajjad; Abdal, Sohaib; Ali, Bagh
Rotating flow for hybrid nanofluid over a stretching surface in the presence of magnetic effect is examined numerically. Hybrid nanofluid consists of graphene oxide and molybdenum disulfide in water base fluid. The inclusion of more than one nanoparticle is carried out due to some outstanding features such as astonishing thermal conduction, which are substantial in heat exchangers, nanotechnology, electronics, and material sciences. In order to attain numerical resolution, the partial differential formulation has been transformed into the corresponding ordinary differential equations. By implementation of apposite similarity variables, the classical Runge–Kutta method and shooting argument have been held to yield finding for the dependent quantities. Thermal transportation enhancement is the need of the day, so this study is made to meet the necessity of industries. A velocity component shows an upsurge with raise in the magnetic field parameter. The magnitude of the velocity component for hybrid nanofluid has a lower boundary as compared to single nanofluid. The temperature profile expressed that hybrid nanofluid is more effective than single nanofluid. These investigations are applicable to the field of the biomedical, automotive industry, nuclear cooling systems, and heat exchangers.